2022
DOI: 10.1186/s12989-022-00459-w
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and plasma metabolome changes in rats after oral gavage of nanoparticles: sensitive indicators of possible adverse health effects

Abstract: Background The oral uptake of nanoparticles is an important route of human exposure and requires solid models for hazard assessment. While the systemic availability is generally low, ingestion may not only affect gastrointestinal tissues but also intestinal microbes. The gut microbiota contributes essentially to human health, whereas gut microbial dysbiosis is known to promote several intestinal and extra-intestinal diseases. Gut microbiota-derived metabolites, which are found in the blood stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…While previous studies have examined the intestinal microbiota after Ag NP exposure, the physiochemical properties of Ag NPs ( e.g. , size, morphology, and coating), experimental models, and conditions were different, leading to different results. ,, Our results showed that after Ag NP exposure, the microbiota profiles increased compared with the control group. Additionally, we found that Ag NP exposure led to an imbalance of intestinal microbiota, which is closely related to the inflammatory reaction and disorder of the intestines.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…While previous studies have examined the intestinal microbiota after Ag NP exposure, the physiochemical properties of Ag NPs ( e.g. , size, morphology, and coating), experimental models, and conditions were different, leading to different results. ,, Our results showed that after Ag NP exposure, the microbiota profiles increased compared with the control group. Additionally, we found that Ag NP exposure led to an imbalance of intestinal microbiota, which is closely related to the inflammatory reaction and disorder of the intestines.…”
Section: Resultsmentioning
confidence: 55%
“…For example, it has been proposed that the actual concentration of silver in tap water was estimated to be 3.05 μg/L . Therefore, many studies have investigated the cytotoxicity profiles of engineered metal NPs on the intestinal system. For example, Landsiedel et al found that oral exposure to Ag NPs and SiO 2 NPs significantly altered the gut microbiome and reduced several genera . Li et al reported that oral exposure to TiO 2 NPs damaged the epithelial structures and acidic mucosal layer in colorectal tissue .…”
Section: Introductionmentioning
confidence: 99%
“…The dysbiosis of the gut microbiota is related to how much mucus is produced, thus decreasing or increasing the possibility of AgNPs presiding in the intestinal barrier. In such cases, AgNPs probably exert detrimental effects on the host via the oral-gut microbiome axis. , For example, van den Brule et al reported that oral exposure to AgNPs affected the gut microbiota of mice with bacterial disturbances similar to those observed in metabolic diseases like obesity, though the detailed mechanism is unclear . Miao et al recently found that AgNPs disturbed the mouse gut microorganisms, causing a decrease in the relative abundance of Bacteroidetes and an increase in the relative abundance of Firmicutes , which are involved in the metabolism of energy, amino acids, organic acids, and lipids, thereby changing liver function .…”
Section: Toxicity Mechanisms and Influencing Factors Of Agnps In The Gitmentioning
confidence: 99%
“…Their findings offer a possible justification for the underlying factors that cause the metabolic disorder after the oral ingestion of AgNPs. In addition, AgNPs can lead to intestinal inflammation in murine models by increasing the abundance of the genera Alistipes , Bacteroides , and Prevotella while decreasing those of Lactobacillus and Akkermansia . , For the human intestinal microbiota, there is only one study assessing the in vitro effects of AgNPs using the stool collected from a healthy donor, showing that the proportions of Raoultella sp . and Escherichia coli increased while those of Bactroides ovatus , Roseburia faecalis , Rosuburia intestinalis , Eubacterium rectale , and Ruminococcus torques decreased .…”
Section: Toxicity Mechanisms and Influencing Factors Of Agnps In The Gitmentioning
confidence: 99%
“…However, metabolomics has been scarcely used in GC research. More and more studies show that metabolites in human uid samples, including in serum and urine, can be important downstream or typical clinical biomarkers in different diseases [22][23][24][25] . Signi cant alterations have been reported in several metabolites of serum and plasma associated with GC, and these metabolites belong to amino acids and their derivatives, represented by tryptophan, glutamic acid, tryptophan and one of its metabolites (kynurenine) [26][27][28] .…”
mentioning
confidence: 99%